2017
DOI: 10.1364/ao.56.008618
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and far-field broadening due to stimulated rotational Raman scattering driven by the Nike krypton fluoride laser

Abstract: Stimulated rotational Raman scattering (SRRS) in the ultraviolet region (λ=248  nm) has been observed at the Nike laser over extended propagation paths in air during high power operation. Although this phenomenon is not significant for standard operating configurations at Nike, broadening of the laser spectrum and far-field focal profiles has been observed once the intensity-path length product exceeds a threshold of approximately 1  TW/cm. This paper presents experimental results and a new theoretical evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…3 for 50m of 200mbar Xe is comparable to that seen in Ref. [2] for beam propagation through a 100m air path.…”
Section: Numerical Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…3 for 50m of 200mbar Xe is comparable to that seen in Ref. [2] for beam propagation through a 100m air path.…”
Section: Numerical Resultssupporting
confidence: 85%
“…The simulation parameters are listed in Table 1 and correspond to the incident beam in Ref. [2]. Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, recent experiments have successfully demonstrated that stimulated rotational Raman scattering can increase the bandwidth of high-energy lasers. 5 This summary presents a numerical study of absolute instability thresholds for SRS and TPD using a broadband pump beam. The calculations suggest that the absolute thresholds can be increased significantly with +1% bandwidth at ICF-relevant conditions.…”
mentioning
confidence: 99%
“…This effect has recently been observed in the ultraviolet region on the Nike kryptonfluoride (KrF) laser at the U.S. Naval Research Laboratory (NRL) [46] with only a modest degradation of the final focal distribution and may provide a practical approach for bandwidth enhancement on other, existing, direct-drive laser facilities [36,40].…”
mentioning
confidence: 99%